Metacognitive Strategies Employed by English Students in Reading Comprehension - Devina Septiani; Azhar Aziz Lubis; Sufiyandi, Sufiyandi (UNIB Press, 2023)
This research aims to investigate the metacognitive strategies employed by English students at Bengkulu University in reading comprehension. This research was a descriptive quantitative study with the design was survey. The design intends to describe the students’ frequencies in employing metacognitive strategies and also the students’ awareness of metacognitive strategies appropriateness in reading comprehension. The population of this study was English students in KIP Faculty at Bengkulu University. The sample was 92 of English students overall. The sample was taken by using simple random sampling technique. The data were collected by using MARSI questionnaire by Mochtari & Reichard. The data obtained from questionnaire was analyzed by using scoring rubric of MARSI questionnaire and used mean formula to calculate the students’ results. The results have revealed that students highly preferred to employ Problem Solving Strategies (3.00) in reading. Global Reading Strategies was the medium strategy preferred by students (2.88). The least strategy preferred by students was Support Reading Strategies (2.82).The result also indicated that English students are frequently employee metacognitive strategies in reading. As conclusion, this study has revealed that students most frequently employed problem-solving strategies (PROB). The study has also found that students have medium awareness of metacognitive strategies appropriateness in reading.